2018
DOI: 10.15761/tcrc.1000102
|View full text |Cite
|
Sign up to set email alerts
|

Fast onset of relief after topical phenytoin in neuropathic pain after chemotherapy

Abstract: During or after chemotherapy, a peripheral neuropathy might rise. Neuropathic pain in such cases is often difficult to treat, and pain is sometimes even increasing in intensity after the cessation of chemotherapy. In 2016 we started a topical phenytoin project to treat pain due to chemotherapy induced peripheral neuropathy (CIPN) and meanwhile we monitored the efficacy and safety of a special phenytoin 5% or 10% cream in great detail in 6 patients suffering from CIPN. We will present in some detail one exempla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…A variety of topical preparations have been investigated in CIPN. These include a baclofen with amitriptyline plus ketamine organogel (BAK) combination [37], low-concentration menthol [38, 39], phenytoin [40], an amitriptyline and ketamine cream [41] and topical combinations of α 2 -adrenergic receptor agonists or nitric oxide (NO) donors combined with either phosphodiesterase (PDE) or phosphatidic acid (PA) inhibitors [42].…”
Section: Introductionmentioning
confidence: 99%
“…A variety of topical preparations have been investigated in CIPN. These include a baclofen with amitriptyline plus ketamine organogel (BAK) combination [37], low-concentration menthol [38, 39], phenytoin [40], an amitriptyline and ketamine cream [41] and topical combinations of α 2 -adrenergic receptor agonists or nitric oxide (NO) donors combined with either phosphodiesterase (PDE) or phosphatidic acid (PA) inhibitors [42].…”
Section: Introductionmentioning
confidence: 99%
“…Recently we demonstrated that it can be of use to apply topical formulations containing phenytoin, a broad acting sodium channel blocker, in pain due to CIPN. Phenytoin application resulted in a fast onset of action; within a time frame of 30 minutes, patients report clinical relevant reductions of pain [5][6][7]. This quick onset of action suggests indeed a local effect on the structures in the epidermis, such as the keratinocytes and the nociceptors (Figure 1).…”
Section: Ngf As a Key Messenger Molecule In Peripheral Sensitizationmentioning
confidence: 98%
“…In the past we reported a number of patients suffering from burning pain in both feet due to CINP, pain which did not subside after months or years following the chemotherapy. Topical treatment with phenytoin 10% diminished the pain considerably, and increased quality of life [5][6][7]. It might be that an ex juvantibus approach using topical phenytoin,could result in relevant pain reduction in a subcohort of CIPN patients, in case of a close fit between phenytoin's mechanism of action and the pathophysiology of CIPN pain.…”
Section: Introductionmentioning
confidence: 99%